USULAN SPESIFIKASI CAMPURAN BERASPAL PANAS ASBUTON LAWELE UNTUK PERKERASAN JALAN - Madi Hermadi; M. Sjahdanulirwan (Direktorat Bina Teknik Jalan dan Jembatan, 2008)
The biggest deposit of Asbuton (natural asphalt from Buton island) located in Lawele Region, it is called As buton Lawele, which has deposit about 100.000.000 tons. Compared to Asbuton Kabungka (the raw material of Granular Asbuton BGA which has met Special Specification of Hot Mix Asbuton). Asbuton Lawele relatively has higher bitumen content, higher light oil content, and higher bitumen penetration value. It has 30% bitumen content, 7% light oil content, and bitumen penetration value of 180 dmm. As Asbuton Lawele has special characteristic, there could be a special specification in order to use it for hot mix asphalt pavement. For that reason, based on the result of laboratory study, in this paper the Specification of Hot Mix Asbuton Lawele is proposed and with the reasons. Based on laboratory study, it is found that Hot Mix Asbuton Lawele hasrelatively similar characteristic with Hot Mix Asphalt Oil Pen 60/70, except the higher value of its Marshall Stability and Dynamic Stability. Hot Mix Asbuton Lawele has Marshal Stability value of 1030 kg, and Dynamic Stability of 3500 passing/mm. Whereas, Hot Mix Asphalt Pen 60/70 has Marshall Stability value of 930 kg, and Dynamic Stability of 1432 passing/mm. Keyword: Road pavement, Hot mix asphalt, Asbuton Lawele